Avaliação da sensação posicional de articulações dos membros superiores em sujeitos expostos cronicamente ao metilmercúrio - OLIVEIRA, Alexandre Rodrigo Batista (Universidade Federal do Pará, 2017)
The Exposure of mercury in some watersheds in the Amazon has chronic character and a mild and moderate intensity. Communities of the basin in the Tapajos River has been monitored about the levels of mercury in the hair over the past 20 years and it was observed that the concentration of mercury in the hair of these people has high levels when compared with other riparian regions, without gold mining activities. In accidents occurred on Minamata in Japan, one of the most common symptoms was the loss of the somestetic function. Proprioception is a somestetic function that can be used to monitor the effects of prolonged exposure to mercury in populations. This work aims to study the sensation of positional joints of upper limb of subjects chronically exposed to mercury and with high levels in the last 3 years and compare the results of this assessment with those obtained in populations with less exposure to methylmercury. Fifty-seven volunteers have agreed to participate in this study, 23 of which belonged to group subjects chronically exposed to mercury from the community of barriers and 34 subjects belonged to the group with lower exposure to mercury from the community of Alter do Chão. Each subject had the positional sensations of joints of the shoulder, elbow and wrist evaluated by 3 times under conditions of open and closed eye. The evaluation consisted of teaching the subject to move a segment of the upper limb (forearm, hand or arm) from a neutral position to a position to articulate target. Each time the subject ended the movement was photographed the final position with digital photo camera of high resolution spatial and temporal. To calculate the articular amplitude at the end of the movement was used the program KINOVEA®, in which allows you to open the photo and use a digital tool to measure the angulation between the proximal and distal segment of the joint in question. Middle articular amplitude values for the open eye condition were statistically higher in the exposed group than in the control group in all the joints, while for the closed eye condition the values exposed group was statistically lower than in the control group only in the wrist joint. There was no statistical difference for the relative difference of angular joint positioning values between the study groups in all joints examined. The exposed group showed lower coefficient of variation for the test condition with the eye open in the joints of the wrist and elbow. The exposed group showed the highest coefficient of variation for the test condition with the eye closed only in the wrist joint. The angular difference values were sequentially higher proximal joints to the distal articulation in the exposed group, however in the control group the angular difference was similar in all the joints. The subjects chronically exposed to mercury showed slight alterations of the joint position sensation when compared with a control group. Proprioceptive evaluation can be an inexpensive tool for the assessment of the effects of mercury on the health of coastal populations exposed to the metal.